До питання картування розповсюдження забруднення від сховищ відходів у верхній частини розрізу - Білашенко, О.Г. (Геотехническая механика, 2012)
Проведен анализ основных путей распространения загрязнения от хранилищ отходов в
верхнюю часть разреза. Исследованы особенности миграции загрязнения по подземным водоносным горизонтам, обоснованы эффективные геофизические методы для исследования ореола загрязнения. The major pathways of pollution distribution from waste storage in the upper part of the section
were analysed. The features of the underground waters migration of pollution are researched. Effective geophysical methods for the study of contamination area are substantiated.